Fundamental solutions for Schrödinger operators with general inverse square potentials. Issue 5 (4th April 2018) - Chen, Huyuan; Alhomedan, Suad; Hajaiej, Hichem; Markowich, Peter
Abstract : In this paper, we clarify the fundamental solutions for Schrödinger operators given as, where the potential V is a general inverse square potential in with . In particular, letting, where, we discuss the existence and nonexistence of positive fundamental solutions for Hardy operator, which depend on the parameter t .